2018
DOI: 10.1080/13816810.2018.1474367
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of candidate genes ZEB1 and LOXHD1 in late-onset Fuchs’ endothelial corneal dystrophy in an Indian cohort

Abstract: While mutations in ZEB1 contributed to 2% of the late-onset FECD cases, the exact role of the two VUS identified in ZEB1 and LOXHD1 in FECD pathogenesis needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…However, in the four families we have studied, all the patients and the family members with normal hearing but carrying a single heterozygous mutation in the LOXHD1 gene showed no corneal abnormalities. Other studies also reported no symptoms of FCD were observed in the probands and their blood-related relatives [7,10,33]. Although the relationship of LOXHD1-related hearing loss and FCD is still unclear, we suggest that ophthalmologic examinations should be performed in patients with ARNSHL when LOXHD1 is suspected to be the pathogenic gene.…”
Section: Discussionmentioning
confidence: 61%
“…However, in the four families we have studied, all the patients and the family members with normal hearing but carrying a single heterozygous mutation in the LOXHD1 gene showed no corneal abnormalities. Other studies also reported no symptoms of FCD were observed in the probands and their blood-related relatives [7,10,33]. Although the relationship of LOXHD1-related hearing loss and FCD is still unclear, we suggest that ophthalmologic examinations should be performed in patients with ARNSHL when LOXHD1 is suspected to be the pathogenic gene.…”
Section: Discussionmentioning
confidence: 61%
“…Mutations in SLC4A11 contribute to approximately 11% and mutations in LOXHD1 contribute to 2% of the FECD cases in this study. A comparison of the role of ZEB1 across multiple ethnicities shows that the contribution of this gene in our Indian population is concurrent with other reports (Rao et al, 2018). In another study it was found that the single nucleotide polymorphisms (SNPs) of TCF4 gene, rs613872 and rs1759573 were associated with a higher risk of sporadic late‐onset FECD in Indian patients (Rao, Tharigopala, Rachapalli, Rajagopal, & Soumittra, 2017).…”
Section: Corneal Dystrophiessupporting
confidence: 92%
“…In 2012, Riazuddin, et al first reported a heterozygous damaging variant within LOXHD1 in a multiplex family with dominant-inherited late-onset FCD [27]. However, subsequent studies failed to provide a strong association between LOXHD1 variants and FCD [20, 2830]. Specially, results from a Chinese multi-generational FCD pedigree demonstrated that no pathogenic variants were identified in LOXHD1 [28].…”
Section: Discussionmentioning
confidence: 99%